2021
DOI: 10.52586/4950
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin superfamily proteins: roles in osteosarcoma

Abstract: Background: Osteosarcoma is a common bone tumor with extremely high malignancy, occurring mostly in children and adolescents. At present, the survival rate of osteosarcomas has made progress in some aspects; however, this can only be regarded as a partial success because substantial progress has not been made in the last few decades. Object: The kinesin superfamily is a group of proteins that play regulatory roles in various metabolic processes and are closely related to tumor metastasis. Increasing evidence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Currently, osteosarcoma accounts for approximately 2.4% of malignancies in children and adolescents worldwide [ 3 ]. Osteosarcoma is characterized by the presence of spindle-shaped stromal cells and osteoid [ 4 ]. And the typical symptoms of patients are local swelling, pain and functional limitation.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, osteosarcoma accounts for approximately 2.4% of malignancies in children and adolescents worldwide [ 3 ]. Osteosarcoma is characterized by the presence of spindle-shaped stromal cells and osteoid [ 4 ]. And the typical symptoms of patients are local swelling, pain and functional limitation.…”
Section: Introductionmentioning
confidence: 99%
“…Osteosarcoma (OS) is the number one primary malignant bone tumor among orthopedic tumors, and those who are susceptible to this disease are children and adolescents, whose 5-year survival rate is less than 20% if it metastasizes 1 , 2 . It has been shown that immune dysregulation in the body is associated with the development of osteosarcoma, and improving the survival of patients with osteosarcoma has long been considered challenging, although treatment of this disease has also improved in recent years, and immune checkpoint inhibition may enhance the therapeutic effect on OS by improving immunosuppression as well as the tumor microenvironment 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, OS is prone to local invasion and early metastasis, mainly affecting the lung and skeleton. Additionally, local recurrence, metastasis, and chemotherapy resistance are associated with poor prognosis (3,4). Despite signi cant improvements in treatment strategies in recent years, treatment outcomes for patients with metastatic or recurrent OS remain pessimistic, with a rather grim prognosis and greatly reduced 5-year overall survival rate of only 20-30% (5,6).…”
Section: Introductionmentioning
confidence: 99%